A retrospective review of the surgical management of tubal ectopic pregnancies at a tertiary Hospital in the Western Cape - Johnson, Ilana (Stellenbosch : Stellenbosch University, 2017, 2017)
Thesis (MMed)--Stellenbosch University, 2017